2023
DOI: 10.26668/businessreview/2023.v8i5.1679
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Banking Institutions and their Role in Economic Development of Jordan

Abstract: Purpose:  This study aimed to demonstrate the importance of economic financing at Islamic banks in the Hashemite Kingdom of Jordan.   Theoretical framework:  This study came to answer the following main questions: What is Islamic banking finance, its meaning, and its characteristics? What is the reality of Islamic banking finance in Jordan? What is the impact of Islamic banking finance in Jordan on increasing investment and saving? What is the impact of Islamic banking finance in Jordan in reducing inflation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The study by Soumadi & Al Smadi (2023) found that financing in Jordanian Islamic banks did not have a statistically significant impact on the gross domestic product and inflation. However, it did demonstrate a statistical influence of financing in Islamic banks on the public commercial sectors, housing, and construction.…”
Section: Literature Reviewsmentioning
confidence: 95%
“…The study by Soumadi & Al Smadi (2023) found that financing in Jordanian Islamic banks did not have a statistically significant impact on the gross domestic product and inflation. However, it did demonstrate a statistical influence of financing in Islamic banks on the public commercial sectors, housing, and construction.…”
Section: Literature Reviewsmentioning
confidence: 95%
“…Indonesia. Pancasila is a unifying symbol for the global community to respect and respect each other on the basis of the spirit of diversity in ethnic diversity, mass organizations also have the principle of struggle as an organization that is in synergy and does not conflict with Pancasila, and makes Pancasila the principle of the organization it forms (Soumadi & Smadi, 2023). Organizations in the Islamic concept are a means of delivering messages to the people or society quickly and accurately (Ismail, 2019).…”
Section: Organization Of Community: An Epistemological Studymentioning
confidence: 99%
“…Currently, approximately 526 Islamic banks worldwide manage assets and consumer funds. (AME Info, 2005) The expansion of Islamic banks demonstrates their success (Soumadi & Smadi, 2023).…”
Section: Introductionmentioning
confidence: 99%